The Use of Demonstration Methods in Improving the Learning Skills Embroidering Simple Patterns in Hearing Resistance Students in Skh Negeri 02 Kota Serang - Syabila Putri; Yuni Tanjung Utami; Toni Yudha Pratama (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2021)
This research is an experimental study with a quantitative approach with the design of One Group Pre-test and Post-test. The study aims to determine the influence of demonstration methods in improving simple pattern embroidery skills in children's hearing resistance. The subjects in this study were hearing barrier students of SMPLB class VII level in SKh Negeri 02 Kota Serang which amounted to 3 people. Based on the results of inferesial statistical analysis using the wilcoxon test formula (t) to indicate that Thitung = 0 and based on the critical value for the wilcoxon test at the significance level of 0.05 with the sum N < 6, obtained Ttabel = 0, then H0 is rejected because Thitung = Ttabel This means that the hypothesis proposed in this study is accepted. This shows that the demonstration method is influential in improving the simple pattern embroidery skills of deaf children in SKh Negeri 02 Kota Serang.